Metode Penyuluhan Dalam Adopsi Inovasi Inseminasi Buatan (Ib) Pada Usaha Peternakan Sapi Di Kabupaten Dharmasraya - Ediset Ediset; Jaswandi Jaswandi (State Islamic University of Sultan Syarif Kasim Riau, 2017)
This research was conducted in the area Dharmasraya Regency, West Sumatra Province. The purpose of this study determined : a) Method of extention in innovation adoption of artificial insemination (AI) in the cattle farm in the District Dharamasraya, and b) Social and economic factors that influence adoption of innovation Artificial Insemination (AI) in the cattle farm in the District Dharmasraya. This research used survey method and approach to the analysis of secondary data. The number of samples in this study were determined by quota sampling technique by reason of homogeneous samples, the farmers were already adopting innovations and cattle ranchers IB program participants snapping Birahi Artificial Insemination (GBIB) thus took a sample of 40 people. The data collected were primary data with the help of question naires and secondary data with the literature study and related agencies. Descriptive analysis of quantitative data which was calculated using a Likert scale. The results showed that the extension method in the adoption of IB in cattle breeding business in the Regency Dharmasraya been implemented, namely the extension methods home and farm visits with category, extension methods demonstrations by both categories, and the campaign extension methods with the medium category. Social and economic aspects such as business scale farmers, revenue, risk, active participation in the innovation adoption had no effect on aspects of the IB whereas age despite being influential in the adoption of innovation, but still in the category of less influential.